IMPLEMENTASI KURIKULUM TAHFIDZ DI MI MANBAUL ULUM - Muhammad Nur Bain; Mushonef , Mushonef; Azwirotul Mubarokah (Journal of Innovation Research and Knowledge, 2024)
The curriculum is an important element in the educational process, because without a curriculum, education will look chaotic and unstructured. The curriculum reflects the philosophy and outlook on life of a nation, which determines the direction and form of the nation's life in the future. Therefore, the educational curriculum must be dynamic and continuously evolving to keep up with changes occurring in global society, and produce achievements that meet expectations. This research will discuss the implementation of the Tahfidz local content curriculum, which is implemented at MI Manbaul Ulum Tlogorejo. This type of research is qualitative research which aims to describe how the Tahfidz local content curriculum is implemented at MI Manbaul Ulum Tlogorejo. Data collection techniques were carried out through interviews with the head of the madrasah, head of curriculum, subject teachers, and two representatives of class VI students. The research results show that MI Manbaul Ulum Tlogorejo began implementing the Tahfidz local content curriculum in the 2021/2022 academic year. The achievement of implementing the Tahfidz curriculum is that all graduates of MI Manbaul Ulum Tlogogrejo have a minimum memorization of juz 30.